The Influence of the Contextual Teaching and Learning Approach on Students Social Sciences Learning Outcomes - Sry Anriyani; Muh. Yahya; Syarifuddin Syarifuddin (JURNAL PENDIDIKAN IPS, 2023)
In social studies classes, students' learning outcomes may be impacted by the absence of learning variables used during the teaching process. The aim is to find out how the application of a CTL-based learning approach can influence students' social studies learning outcomes. This research adopts a quasi-experimental research type with a non-equivalent pretest-posttest research design. The sampling technique was carried out purposively on a population of 91 students, resulting in two sample groups including class VIIIa as the experimental group with 30 students and class VIIIb as the control class with 30 students. The instrument used as a data collection tool is an essay test. Data analysis techniques use descriptive statistical analysis techniques and inferential statistics (hypothesis testing). The research results obtained in the form of descriptive statistics show that of the 13 statements regarding the implementation of contextual learning and learning, 7 implementation statements are included in the Effective category, 2 statements in the very effective category, and 4 statements in the Quite Effective category. The results of this observation show that the implementation of contextual learning and learning of social studies subjects is going well. The results of hypothesis testing for social studies learning outcomes through an independent sample t-test show that Sig. count < α or 0.013 < 0.05, which means that there is a significant influence of contextual learning and teaching approaches on the average value of social studies learning outcomes for experimental group students.